Longitudinal shape irregularity of airway lumen assessed by CT in patients with bronchial asthma and COPD. Issue 8 (29th May 2015) - Oguma, Tsuyoshi; Hirai, Toyohiro; Fukui, Motonari; Tanabe, Naoya; Marumo, Satoshi; Nakamura, Hajime; Ito, Hisao; Sato, Susumu; Niimi, Akio; Ito, Isao; Matsumoto, Hisako; Muro, Shigeo; et al.
Abstract : Background: Airway remodelling in bronchial asthma (BA) and COPD has been quantitatively assessed by analysing the airway wall area and the luminal area on cross-sectional CT images. To date, there have been no reports on assessment of the longitudinal structure of the airway lumen. Methods: Quantitative airway analysis using CT was performed on three groups consisting of 29 patients with BA, 58 patients with COPD and 59 healthy controls. To assess the longitudinal shape irregularity of the airway lumen, new quantitative CT parameters, validated by a phantom study, were established. The internal radii of imaginary inscribed spheres in the airway lumen were measured as a function of distance from the level of the carina to the fifth-order branches of the right posterior basal bronchus. The gaps of these radii from the regression line were calculated as parameters to reflect the longitudinal airway lumen shape irregularity. These new parameters were compared among the study groups as well as with the conventional parameters of airway wall thickening and luminal area. Results: Longitudinal airway lumen shape irregularity was significantly greater in patients with COPD than in those with BA and healthy controls. Wall thickening was significantly greater, and luminal area smaller, in patients with BA than in those with COPD and healthy controls. These results were consistent even among the BA and COPD subgroups with similar airflow limitation. Conclusions: The combination of cross-sectional and longitudinal airway structure analyses using CT images may suggest differences in the characteristics of airway remodelling between COPD and asthma.